Leaching Study Of Precious Metal Recovery From Ferric Permanent Magnet Waste - Hisyam, A.; Ismail, N. A.; Mohd Taib, M. K. A.; Shariff, S. (Asian Research Publishing Network (ARPN), 2016)
This paper describes the characterization and leaching behavior of precious metal present from electronics scrap to obtain liquor which can be treated through hydrometallurgical techniques to purify the metals. The results of this study points out the technical feasibility of the recovery of the metals. The blank sample was characterized by X-ray florescence. This paper will also present the results of hydrometallurgical extraction experiments, which allow the recovery of rare earth element. Inductively Coupled Plasma–Mass Spectrometry (ICP-MS) was used in order to determine the element composition in the leaching process in term of molarity, temperature, and acid solvent. Two leachants were compared (sulfuric acid and hydrochloric acid) at different molarity (1 M, 2 M and 5 M) and different temperature (room temperature, 50 0C and 100 0C). It was found that sulfuric acid leaching was very promising as a leachant for recovery of Fe, Cu, Si, Ti and Nb metal at room temperature . At higher concentration, hydrochloric acid allowed the leaching up to almost 40% of Ti, 60% of Nb and impressively 200% of P more than H2SO4. The results shows that the hydrometallurgical recovery of precious metals present in permanent magnet is a technically feasible.